KOMUNIKASI PERSONAL TERHADAP NILAI TRANSAKSI DAN KEPUASAN KONSUMEN - Kusuma, Anuraga (prodima@fe.uika-bogor.ac.id, 2020)
The purpose of this study is to see how the personal communication of MSMEs jelly milk in Tanah Sareal Kota Bogor district on transaction value and customer satisfaction. In this study found as many as 20 customer samples were interviewed 18 people who have confidence in jelly milk products marketed in Tanah Sareal sub-district, Bogor City. While the value of consumer transactions increases by 20% every week. This study shows that personal communication practiced from the dairy food business in Tanah Sareal, Bogor City, was a consumer supporting factors for conducting transactions and satisfaction with jelly milk products.